(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
A significant number of applications in the electric power drive sector face reduced performance and capabilities due to cost issues. In these cases, accurately tracking a position or speed command is difficult due to the low resolution of position sensors. In addition, low-speed drives using brushless synchronous motors exhibit torque ripple due to the physical construction of the motors and magnetic interactions between the stator and rotor. The proposed solution seeks to minimize the effect of these torque disturbances by identifying and compensating for them in real time using a disturbance observer.